PENGGUNAAN WAGO DAN GAIRAIGO PADA BAHASA JEPANG PARIWISATA - Merta Pebrima, I Wayan (Humanis, 2016)
Abstract This research analized the “Usage of Wago and Gairaigo in Japanese for Tourism”. The purpose of this research is to find the similarities and differences of the meaning of the word of wago and wairaigo, and to know  the usage of wago and gairaigo by tourism workers in Bali who use Japanese . The results of this research indicate that  wago and gairaigo are mutually influential in the field of tourism. Most of the wago and gairaigo words are synonymous and have similarities and differences of meaning. The usage of wago and gairaigo  by tourism workers in Bali are influenced by various factors such as age, social status, or circumstances.
Keywords: ruigigo, wago, gairaigo, language variety